2016
DOI: 10.1002/cne.23955
|View full text |Cite
|
Sign up to set email alerts
|

Organization of projection neurons and local neurons of the primary auditory center in the fruit flyDrosophila melanogaster

Abstract: Acoustic communication between insects serves as an excellent model system for analyzing the neuronal mechanisms underlying auditory information processing. The detailed organization of auditory neural circuits in the brain has not yet been described. To understand the central auditory pathways, we used the brain of the fruit fly Drosophila melanogaster as a model and performed a large-scale analysis of the interneurons associated with the primary auditory center. By screening expression driver strains and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 80 publications
(185 reference statements)
1
42
0
Order By: Relevance
“…To test whether the combination of the projecting subareas of JO neurons was correlated with the somata location, we visualized single JO-A neurons using the “heat-shock FLP-out” technique, which restricts reporter expression to one or only a few GAL4-expressing cells (Basler and Struhl, 1994; Wong et al, 2002; Kamikouchi et al, 2006; Matsuo et al, 2016). To include as many neurons as possible, we also used JO15 strain, which labeled JO-A and JO-B neurons (Kamikouchi et al, 2006), for this single-cell analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test whether the combination of the projecting subareas of JO neurons was correlated with the somata location, we visualized single JO-A neurons using the “heat-shock FLP-out” technique, which restricts reporter expression to one or only a few GAL4-expressing cells (Basler and Struhl, 1994; Wong et al, 2002; Kamikouchi et al, 2006; Matsuo et al, 2016). To include as many neurons as possible, we also used JO15 strain, which labeled JO-A and JO-B neurons (Kamikouchi et al, 2006), for this single-cell analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A large-scale analysis of secondary auditory neurons in the brain identified 19 types of interneurons downstream of JO-A neurons, all of which innervate specific subarea(s) in zone A (Matsuo et al, 2016). Given that one subarea receives projections from several types of JO-A neurons, the differently filtered auditory information could be integrated in these downstream neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dendrites of aPN3 neurons reside in the brain region targeted by JON axons (Figure S2) and are reported to overlap with the E branch of the JON axon bundle (Matsuo et al, 2016; Vaughan et al, 2014). We began by reexamining the overlap between JON axons and aPN3 neuron dendrites.…”
Section: Resultsmentioning
confidence: 99%
“…We found that stimulating the C/E JONs evoked a mixture of excitation and inhibition (Figure 1F). Excitation typically preceded inhibition, which suggests a direct excitatory input from the E and possibly also C JON axon branches, as well as an indirect inhibitory input via interposed inhibitory interneurons in this brain region (Matsuo et al, 2016). Interestingly, excitation dominated some aPN3 neurons, whereas inhibition dominated others.…”
Section: Resultsmentioning
confidence: 99%